Controlling the Growth of Metal‐Organic Frameworks Using Different Gravitational Forces. Issue 27 (4th July 2016) - Richardson, Joseph J.; Liang, Kang; Lisi, Fabio; Björnmalm, Mattias; Faria, Matthew; Guo, Junling; Falcaro, Paolo
Abstract : Control over Metal‐organic framework (MOF) size and morphology is interesting for both fundamental and applied science. Gravitational force ( g ) is generally acknowledged as an interesting parameter for controlling crystal size; however, a dedicated study on the effect of g on MOF synthesis is missing. Here, we investigate the effect of varied g (< 1, 1, 20, 50, and 100) during the crystallization of different MOFs [ZIF‐8, Tb2 (BDC)3 and HKUST‐1] in solution. The obtained MOFs were investigated using dynamic light scattering (DLS), X‐ray scattering (SAXS and WAXS), and scanning electron and optical microscopy (SEM and OM, respectively). When compared with standard g ( g = 1), high g ( g = 20) gave rise to the formation of smaller MOF crystals, while low g ( g < 1) led to larger crystals likely due to facet‐oriented crystal fusion. This demonstrates that gravity and g ‐force can be used to rationally control the size of different MOFs by increasing or decreasing convection (mass transfer) and sedimentation. Abstract : Metal‐organic frameworks (MOFs) are grown under different gravitational forces. We demonstrate that larger MOFs grow at lower g ‐force ( g < 1), while smaller MOFs grow at higher g ‐force ( g = 20). This data matches well with historical studies on crystal growth in microgravity, suggesting that the MOFs explored herein are governed by similar growth mechanisms to a wide variety of other crystals.